Evaluating the biological risk of functionalized multiwalled carbon nanotubes and functionalized oxygen-doped multiwalled carbon nanotubes as possible toxic, carcinogenic, and embryotoxic agents - Lara-Martínez, Luis A (Int J Nanomedicine, 2017)
Carbon nanotubes (CNTs) have been a focus of attention due to their possible applications in medicine, by serving as scaffolds for cell growth and proliferation and improving mesenchymal cell transplantation and engraftment. The emphasis on the benefits of CNTs has been offset by the ample debate on the safety of nanotechnologies. In this study, we determine whether functionalized multiwalled CNTs (fMWCNTs) and functionalized oxygen-doped multiwalled CNTs (fCOxs) have toxic effects on rat mesenchymal stem cells (MSCs) in vitro by analyzing morphology and cell proliferation and, using in vivo models, whether they are able to transform MSCs in cancer cells or induce embryotoxicity. Our results demonstrate that there are statistically significant differences in cell proliferation and the cell cycle of MSCs in culture. We identified dramatic changes in cells that were treated with fMWCNTs. Our evaluation of the transformation to cancer cells and cytotoxicity process showed little effect. However, we found a severe embryotoxicity in chicken embryos that were treated with fMWCNTs, while fCOxs seem to exert cardioembryotoxicity and a discrete teratogenicity. Furthermore, it seems that the time of contact plays an important role during cell transformation and embryotoxicity. A single contact with fMWCNTs is not sufficient to transform cells in a short time; an exposure of fMWCNTs for 2 weeks led to cell transformation risk and cardioembryotoxicity effects.